ANALISIS MANAJEMEN RISIKO DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE (STUDI KASUS PADA PT ANGKASA PURA I (PERSERO)) - Khristian, Edwin; Karamoy, Herman; Budiarso, Novi Swandari (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to analyze risk management at PT Angkasa Pura I (Persero) in realizing Good Corporate Governance (GCG). This research is a qualitative research with a case study approach. Data were obtained through in-depth interviews, observation and documentation studies. The results show that PT Angkasa Pura I (Persero) has a unit that manages risks specifically and has risk management guidelines based on SNI ISO 31000: 2018. In conducting the research, the authors limit the risk management analysis only to the principles of risk management and from the analysis results it is known that the company has implemented 7 (seven) risk management principles according to SNI ISO 31000: 2018 which is the Company's Risk Management Guidelines. There is one risk management principle that has not been perfectly implemented by the company, namely the principle of inclusiveness/involving all parties, because the company has not clearly invited the involvement of external stakeholders in carrying out its risk management. In improving the risk management process, there is a role for internal audit that can improve the risk management process, namely ensuring objective assurance and the adequacy of the risk management process. The company applies the concept of three lines of defense and risk-based auditing in carrying out internal control functions, this shows the close relationship between risk management and internal audit which places risk management as the second line of defense and internal audit as the third line of defense. Repeated audit findings and audit recommendations that cannot be followed up as well as self-awareness of all company personnel are problems that arise and need to be considered by the Company in implementing risk management. The implementation of Key Performance Indicators in all business units and training to raise awareness about risk management is an option for the company as an effort to overcome this, so that the implementation of risk management can be even better.